Sarcomatoid Tumor following Radium Treatment - Wahida Chakari; Anette Pedersen Pilt; Jørgen Lock-Andersen (Karger Publishers, 2018)
Haemangiomas are benign skin lesions that usually regress spontaneously, but radiotherapy has previously been used to assist the regression and healing of the lesions. Radium and X-rays were used as a treatment for benign skin lesions such as haemangioma until the carcinogenic effect of ionising radiation in humans was described. We report a patient diagnosed with a sarcomatoid carcinoma. Her past history was of particular interest since she had received radium treatment for a haemangioma at the same location more than 70 years before.